2014
DOI: 10.1128/jcm.02935-13
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Campylobacter in Stool and Determination of Significance by Culture, Enzyme Immunoassay, and PCR in Developing Countries

Abstract: iCampylobacter is a common bacterial enteropathogen that can be detected in stool by culture, enzyme immunoassay (EIA), or PCR. We compared culture for C. jejuni/C. coli, EIA (ProSpecT), and duplex PCR to distinguish Campylobacter jejuni/C. coli and non-jejuni/coli Campylobacter on 432 diarrheal and matched control stool samples from infants in a multisite longitudinal study of enteric infections in Tanzania, Bangladesh, and Peru. The sensitivity and specificity of culture were 8.5% and 97.6%, respectively, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 28 publications
1
77
0
4
Order By: Relevance
“…In the case of stool antigen tests for Campylobacter antigen detection, cross-reactivity with species of Campylobacter other than C. jejuni or C. coli has been reported (18)(19)(20)(21), so perhaps these other Campylobacter species present in the stool samples account for discordant results. In our study, we had an insufficient number of other identified species, such as C. upsaliensis (n ϭ 1) and C. showae (n ϭ 1), to make any conclusion about the ability of stool antigen CIDTs to detect these species (see Table S2 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of stool antigen tests for Campylobacter antigen detection, cross-reactivity with species of Campylobacter other than C. jejuni or C. coli has been reported (18)(19)(20)(21), so perhaps these other Campylobacter species present in the stool samples account for discordant results. In our study, we had an insufficient number of other identified species, such as C. upsaliensis (n ϭ 1) and C. showae (n ϭ 1), to make any conclusion about the ability of stool antigen CIDTs to detect these species (see Table S2 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…A study of infants with diarrhea in developing countries of South America found ProSpecT to have 60.6% sensitivity and 88.8% specificity for C. jejuni/C. coli infections (18). Our prospective multicenter study included 2,767 samples with 86 culturepositive patients (3.1% prevalence).…”
Section: Discussionmentioning
confidence: 99%
“…In Peru, a study that included 150 pediatric stool samples from the Etiology, Risk Factors and Interactions of Enteric Infections and Malnutrition and the Consequences for Child Health and Development (MAL-ED) cohort study detected C. jejuni/C. coli in 41.3% of the children with gastroenteritis and 18.7% of the controls (P ϭ 0.007) (45). In contrast, the difference in the prevalences of other Campylobacter species, including C. hyointestinalis subsp.…”
Section: Epidemiologymentioning
confidence: 99%
“…Though cross-reactivity with other Campylobacter species has been reported for stool antigen CIDTs previously, the authors did not investigate this aspect of the analytical specificity of the assays (9)(10)(11)(12). Nonetheless, it is important to consider that noncases were typically not clinically compatible with the positive stool antigen CIDT results, which argues against the idea that false-positive results are largely attributable to pathogenic Campylobacter spp.…”
mentioning
confidence: 45%
“…While some studies have described excellent sensitivity and specificity versus conventional Campylobacter culture, sometimes with enhanced sensitivity compared to culture (5,6), others have reported poor specificity and variable sensitivity (7)(8)(9)(10). Still others have shown that these assays potentially have broader detection within the Campylobacter genus than what the manufacturers have indicated in their instructions for use (further complicating the true analytical performance) (9)(10)(11)(12). This collective body of work has culminated in a quagmire of conflicting/ inconsistent data and even contentious opinions as to the best use of these assays (if any) for clinical care in the diagnosis and reporting of campylobacteriosis.…”
mentioning
confidence: 98%